Penerapan Denda Pada Pembiayaan Murabahah Pada Bank Sumut KCPSY Marelan Raya - Jaya, Rama Indra; Juliati, Yenni Samri (Universitas Labuhanbatu, 2024)
This research explores the pivotal role of banks in managing public funds, emphasizing customers as the primary assets supporting bank growth. The evolution of banking, particularly the establishment of PT Bank Muamalat Indonesia (BMI) as a Shariah-compliant bank in 1992, was initiated by discussions regarding Islamic banking as a pillar of the Islamic economy, involving figures such as Karnaen A Perwataatmadja, M Dawam Rahardjo, AM Saefuddin, and M Amien Azis. The study identifies a phenomenon of customer delays in payments to Shariah-compliant banks providing financing through specific contracts, causing banks losses due to collection costs. In response, Shariah banking management deems it crucial to apply compensatory penalties for these expenses. This research focuses on the application of Shariah principles, especially concerning the imposition of fines in murabahah financing at Bank Sumut KCPSy Marelan Raya, aiming to comprehend the legal basis and practices of applying fines in this context. The research methodology entails a qualitative approach with descriptive analytical methods. Qualitative methods are used to understand the context and Shariah principles underlying murabahah financing, while descriptive analytical methods analyze and explain the imposition of fines in such financing at Bank Sumut KCPSy Marelan Raya. The study involves data collection through literature review, analysis of documents related to relevant Shariah principles, and interviews with stakeholders at Bank Sumut KCPSy Marelan Raya. The research findings encompass a profound understanding of the legal framework and Shariah principles governing murabahah financing, as well as a better comprehension of fine imposition in this context. Moreover, the results unveil practices and policies employed by Bank Sumut KCPSy Marelan Raya in handling cases of delayed payments for murabahah financing and the application of fines as a response to such actions.